2020
DOI: 10.1038/s41598-020-62614-7
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to comprehensively evaluate the morphological properties of the human femoral head: example of application to osteoarthritic joint

Abstract: Osteoarthritis affects the morphological properties of the femoral head. The goal of this study was to develop a method to elucidate whether these changes are localised to discrete regions, or if the reported trends in microstructural changes may be identified throughout the subchondral bone of the human femoral head. Whole femoral heads extracted from osteoarthritic (n = 5) and healthy controls (n = 5) underwent microCT imaging 39 μm voxel size. the subchondral bone plate was virtually isolated to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The morphometric measurements for each specimen are reported in Table 1 . A detailed comparison of the morphometric properties for these OA specimens with healthy specimens can be found in Ryan et al [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The morphometric measurements for each specimen are reported in Table 1 . A detailed comparison of the morphometric properties for these OA specimens with healthy specimens can be found in Ryan et al [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it should be noted that the higher strains seem to localise around the heterogeneous structure of the superior femoral head. Previous studies have shown that microstructural changes within the OA femoral head lead to sclerosis and subsequent increased BV/TV in the subchondral bone with a coincident reduction in BV/TV in regions medial and lateral to the principle loading axis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations